2013
DOI: 10.1016/j.jfoodeng.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high intensity ultrasound application on mass transport, microstructure and textural properties of pork meat (Longissimus dorsi) brined at different NaCl concentrations

Abstract: ElsevierOzuna López, C.; Puig Gómez, CA.; García Pérez, JV.; Mulet Pons, A.; Carcel Carrión, JA. (2013). Influence of high intensity ultrasound application on mass transport, microstructure and textural properties of pork meat (Longissimus dorsi) brined at different NaCl concentrations. Journal of Food Engineering. 119 (1) The aim of this work was to evaluate the effect of high intensity ultrasound and NaCl 28 concentration on the brining kinetics (5±1 ºC) of pork loin as well as its influence on the 29 textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 27 publications
11
93
1
9
Order By: Relevance
“…Increasing the NaCl concentration progressively between 70 and 140 g/L reduced the hardness, while treatments with 200 g/L increased the hardness. Similar trends were obtained by Ozuna et al [18] for pork meat salting at different NaCl concentration in brine, in which this behavior is due to the high concentrations of NaCl in the tissue, which promoted changes in meat texture, leading to harder samples. On the other hand, the application of US during marinating increased the meat hardness.…”
Section: Effect Of Treatments On Whcsupporting
confidence: 87%
See 2 more Smart Citations
“…Increasing the NaCl concentration progressively between 70 and 140 g/L reduced the hardness, while treatments with 200 g/L increased the hardness. Similar trends were obtained by Ozuna et al [18] for pork meat salting at different NaCl concentration in brine, in which this behavior is due to the high concentrations of NaCl in the tissue, which promoted changes in meat texture, leading to harder samples. On the other hand, the application of US during marinating increased the meat hardness.…”
Section: Effect Of Treatments On Whcsupporting
confidence: 87%
“…During the first 60 min of marinating, a faster increased in the NaCl content was observed at all experiments. The same behavior was observed by other authors when salting or marinating with sodium chloride, which was attributed to the large concentration gradient between solution of marinating and meat at the beginning of the salting process [18,19]. When using a marinating solution of 70 g NaCl/L, the NaCl content in the meat after 120 min of process was almost two times lower than when using 140 and 200 g NaCl/L.…”
Section: Effect Of Treatments On Weight Losses and Nacl Contentsupporting
confidence: 85%
See 1 more Smart Citation
“…Denatured protein molecules will aggregate and/or crosslink to form larger clusters and, at high concentrations, will result in the formation of crosslinked amino acids such as lysinoalanine, ornithinoalanine, lanthionine and so on. In particular, ultrasound has been commercially used in different food science applications such as emulsification (Kara et al 2015), dispersion of solids (Pereira et al 2016), crystallization (Sheikh & Patel 2014), acceleration of mass transport processes in mixing (Ozuna et al 2013) and extraction (Dahmoune et al 2015;Kadam et al 2015). As a result, new safe and effective methods of food processing and preservation are being developed.…”
Section: Introductionmentioning
confidence: 99%
“…[10] suggested that, during the marination of pork loin, the application of a lowfrequency (20 kHz) and low-power (2.5 W / cm 2 ) ultrasonic treatment increases the interval between myofibrils to allow more space for water uptake, causing a significant increase in muscle water-binding capacity that in turn contributes to greater meat tenderness. Another study asserted that the cavitation effect induced through ultrasound can be used to modify cell membranes, creating micro-channels and micro-stirting that facilitate the mass transport of marinade and change of meat structure or texture [44,45]. In the present study, the rate of marinade absorption was determined to coincide with the rise of MFI, inferring that the breakage of myofibrils represents damage to meat microstructures, which can promote marinade absorption.…”
Section: Myofibril Fragmentation Index and Marinade Absorption Rate Omentioning
confidence: 50%